2017
DOI: 10.1182/bloodadvances.2016001370
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of HTLV-1 reverse transcriptase activity in ATL patients treated with zidovudine and interferon-α

Abstract: Key Points• The therapeutic efficacy of the AZT and IFN combination in ATL presumably reflects the inhibition of RT-related functions.• HTLV-1-RT activity from short-term cultured PBMCs may represent a predictive correlate of clinical response to AZT/IFN in ATL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
(25 reference statements)
1
18
0
Order By: Relevance
“… 37 Conversely, a recent report demonstrated that the combination AZT/IFN induced a significant inhibition of HTLV-I reverse transcription activity in responding ATL patients but not in resistant patients. 74 These results are in line with a direct antiviral effect, likely in the HTLV-1–infected nonmalignant cells, which may play a major role in the survival of ATL cells.…”
Section: Strategy Of Targeting Therapy: Preclinical Datasupporting
confidence: 72%
“… 37 Conversely, a recent report demonstrated that the combination AZT/IFN induced a significant inhibition of HTLV-I reverse transcription activity in responding ATL patients but not in resistant patients. 74 These results are in line with a direct antiviral effect, likely in the HTLV-1–infected nonmalignant cells, which may play a major role in the survival of ATL cells.…”
Section: Strategy Of Targeting Therapy: Preclinical Datasupporting
confidence: 72%
“…Interestingly, moreover, the capacity of AZT to specifically inhibit retroviral gene expression in cells harboring the HK2 endogenous retrovirus has been reported, suggesting the possibility that the drug could actually affect retroviral mRNA transcription 46 . Our previous study has shown that in ATL patients who responded to therapy with AZT plus IFN, HTLV-1 RT activity was inhibited, while this did not occur in a nonresponder patient (ATL) 47 . This implies that AZT actually acts as HTLV-1 RT-inhibitor in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies of gene expression in individual cells have shown that both allelic expression (42) and transcriptional bursting (43,44) are mechanisms that control gene expression in mammalian cells. The control of gene transcription in latent human T cell leukemia virus type 1 (HTLV-1) infection has shown that retroviral gene expression occurs by a process of burst expression (45). For clonally expanded cells infected with HTLV-1, latency is determined by a balance between the burst expression of Tax and the low-level, persistent expression of HTLV-1 basic leucine zipper factor (HBZ) (45).…”
Section: Discussionmentioning
confidence: 99%
“…The control of gene transcription in latent human T cell leukemia virus type 1 (HTLV-1) infection has shown that retroviral gene expression occurs by a process of burst expression (45). For clonally expanded cells infected with HTLV-1, latency is determined by a balance between the burst expression of Tax and the low-level, persistent expression of HTLV-1 basic leucine zipper factor (HBZ) (45). During reactivation of latent HIV infection, levels of HIV expression depend on both the frequency of bursting and the burst size (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%